An ontology segmentation tool - Simonyi, András; Szőts, Miklós (Acta Cybernetica, 2010)
Extracting a minimal relevant segment of an extensive domain ontology is an often recurring problem in ontology engineering. We present a software solution to this problem that is the combination of an ontology-independent user interface generator and a module implementing an ontology segmentation algorithm. We describe the algorithm and compare it with other ontology segmentation methods proposed in the literature.